Savaşın Değişen Doğası ve Clausewitz: "Savaş Üzerine” Eleştiriler - Öztürk, Mehmet (Muş Alparslan Üniversitesi, 2020)
A war, as a social phenomenon, has managed to find a space for itself in every period of history. Many philosophers, who could not remain indifferent to this, were machsely interested in this reality and put forward their own thesis. One of them was Prussian soldier and theorist Carl von Clausewitz (1780-1831) with the ideas he put forward in his book On War. His study and philosophy have attracted close attention from those interested in war and have been the focus of numerous studies after him. However, the criticisms “on war” were limited in the studies conducted. The aim of this study is to examine the position of Clausewitz’s views in the face of the changing nature of war, based on new and postmodern phenomena of war. In the analysis, it was seen that it was possible to criticize Clausewitz especially through absolute war, trinity, war-politics relationship and rationality.

Sosyal bir olgu olan savaş, tarihin her döneminde kendine bir alan bulmayı başarmıştır. Buna kayıtsız kalamayan pek çok filozof, bu realite ile yakından ilgilenmiş ve kendi tezlerini ortaya koymuştur. Bunlardan birisi, Savaş Üzerine isimli eserinde ortaya koyduğu fikirlerle Prusyalı asker ve teorisyen Carl von Clausewitz (1780-1831) olmuştur. Onun eseri ve felsefesi, savaşla ilgilenen kesimlerin yakın ilgisini çekmiş ve kendinden sonra çok sayıda çalışmanın odağını oluşturmuştur. Bununla birlikte yapılan çalışmalarda “savaş üzerine” eleştiriler sınırlı kalmıştır. Bu çalışma; yeni ve postmodern savaş olgularından yola çıkıldığında savaşın değişen doğası karşısında Clausewitz’in görüşlerinin konumunu incelemeyi amaçlamıştır. Yapılan analizde özellikle mutlak savaş, üçleme, savaş-politika ilişkisi ve rasyonellik üzerinden Clausewitz’e eleştiriler yöneltebilmenin mümkün olduğu görülmüştür.
anemon
Keywords: Clausewitz; On War; New Wars; Postmodern War; Criticism; Clausewitz; Savaş Üzerine; Yeni Savaşlar; Postmodern Savaş; Eleştiri